(Re)assembling Community: The Ontological Politics of Academic and Community-based Research in/on/with/by a Migrant Community in London. (August 2018) - Fransman, Jude
This article explores the ontological politics of research in the field of community studies. Focusing on a migrant community in London, UK, it shows how the community is (re)assembled in different ways through the different research practices of academics and practitioners. Guided by a framework based on material semiotics, this article compares the agendas, methods, and representational texts that inform the different research practices. It argues that community studies researchers have an ethical responsibility to acknowledge the particular enactments of communities that emerge through their research and the role that agendas, methods, and texts play in constructing those enactments.